Australian women's experiences of smoking, cessation and 'cutting down' during pregnancy. Issue 1 (2nd January 2019) - Hansen, Emily C.; Frandsen, Mai; Williams, Danielle; Ferguson, Stuart G.
ABSTRACT: This article presents an analysis of interviews with Australian women who had smoked or were currently smoking during pregnancy. It explores how they spoke about their experiences of smoking, cessation and harm minimisation during pregnancy. Eighteen women underwent a single in-depth interview, these were analysed using an iterative thematic method. We found that smoking, cessation and harm minimisation by pregnant women are complex social practices. Participants viewed smoking as a potential risk to fetal health and as an actual risk to their own health and described feeling embarrassed and ashamed of smoking when pregnant. Their opinions about the relative seriousness of health risks posed by smoking when pregnant were often informed by their own personal observations and experiences. Participants used this knowledge to engage in lay epidemiological processes as they rationalised and made sense of the relative risks of smoking, quitting or cutting down. They also sought legitimacy for their claims about the safety of quitting or cutting down in two potentially contradictory ways. These were personal experience/observations and medical advice. Our findings contribute to sociological understanding about lay responses to medical advice on smoking in pregnancy and will be of value to healthcare professionals who work with pregnant women.